An epidemiological study of protein energy malnutrition among children below six years’ age in an urban slum of Gurgaon, Haryana, India - Kumar, Tarun; Deswal, Balbir Singh (International Journal Of Community Medicine And Public Health, 2016)
Background: Poorly nourished child grows less rapidly during first 6 years of age. In India, around 43% of fewer than five children were underweight. Child protein energy malnutrition reflects a number of intermediately processes such as household access to food, access to health service and caring practices. The present study was undertaken to assess prevalence of PEM as well as the nutritional status of children below six years’ age group and to explore most probable risk factors influencing PEM. Methods: The study was a community based cross-sectional study carried out in 500 randomly selected households in a slum area of Gurgaon among the children below 6 years of age using pretested Performa which contained details regarding socio-demographic, nutritional conditions and utilization of health care services. Nutritional status was assessed by Physical examination, anthropometric measurement, haemoglobin and parasitological (stool) tests. Nutritional grading was done according to by physical and anthropometric examination of child using Indian Academy of Pediatrics (IAP) classification and supplemented by WHO growth chart. Data was entered in the MS Excel sheet and analyzed using Epi info Ver 7. Results: During survey acute illness detected among 0.25% children and chronic illness prevalence was 25%. Prevalence of PEM was found to be 43.86% (37.73% among males, 50.0 % among females). Clinical signs of nutritional deficiency were detected among 31.48 % of children. Common types of nutrition deficiency were anemia, PEM, and vitamin A and B complex deficiencies. Main reasons of PEM were attributed to female sex, poor literacy of parents, low socioeconomic status, higher No. siblings and large family, recurrent diarrhea and other infections, prolonged breast feeding with delayed introduction of supplements particularly semisolid and poor quality of supplements. Intestinal parasite detected among 38.43% of children, commonest parasite being giardia, ascariasis and thread worms; existing health services utilized in 30.72% of total illness. This was identified not due to lack of knowledge but other domestic problems. Conclusions: Prevalence of PEM was attributed to poor living conditions, poor literacy status of parents, higher No. of siblings, poor utilization of health services, poor nutritional services of children and faulty breast feeding and weaning practices in the family. Public health specialists should plan interventions focusing on these issues.